Pengaruh Sistem Informasi Akuntansi, Pengendalian Internal, dan Kompensasi Terhadap Kecurangan Akuntansi Dalam Sistem Pemberian Kredit Pada PT BNI Kota Metro - Kurniawan, Muhammad Shuhada; Zanaria, Yulita; Darmayanti, Elmira Febri (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of accounting information systems, internal controls and compensation for accounting fraud in the credit granting system at PT BNI Kota Metro. The type of research used in this research is quantitative research with an associative approach. Data analysis was carried out by testing instruments, classical assumptions and testing hypotheses. The results of the study show that the Accounting Information System has a significant effect on accounting fraud. Internal control has a significant effect on accounting fraud. Compensation has a significant effect on accounting fraud. Accounting Information Systems, Internal Control, and Compensation simultaneously have a significant effect on accounting fraud.